An Unusual Cause of Vertebral Artery Dissection: Esophagogastroduodenoscopy - Fernando D. Testai; Philip B. Gorelick (Stroke Research and Treatment)
Brain-supplying arterial dissection is considered one of the most common vascular causes of stroke in younger patients. Dissections are usually preceded by trauma or mechanical stress; the vascular stressor may be trivial as this condition has been described in association with manipulation and stretching the neck. Here we describe a case of vertebral artery dissection and stroke following esophagogastroduodenoscopy. This case highlights a potentially serious complication that may occur after procedures that require hyperextension of the neck.